Re-primarization revisited:: an analysis of decision-making variables in the Argentine soy agribusiness (1993”“2015) - Dorn, Felix Malte; Hafner, Robert (Sustainability in Debate, 2018)
Argentine soy production from the 1990s to the 2010s has shown major shifts in both production techniques and the ping-pong-relationships between the agribusiness and national governments. The objective of this paper is to introduce a new statistics-based perspective on soy production in Argentina. We analyse variables of technological innovation, weather, price, territorial expansion, and the role of the state to show the extent of influence these variables have on the decision-making of agribusiness representatives and subsequent production and export of soy. As a result, we show that the primary resource ‘soybean’ does not equal the soy commodities that are exported: National refinement does occur, watering down the re-primarization argument within the debate on neo-extractivism and re-defining the actual role of national governments from steering power of ‘what’ and ‘how much’ is produced to ‘in what form’ soybeans are exported.